MEDIA SOSIAL SEBAGAI SARANA PEMASARAN - Cut Devi Maulidasari; Muhammad Rahmat Hidayat (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2019)
In its development of technology and social media is another alternative for someone to market their products more broadly, one of the product advertisements in the online world can also be in the form of long writing written by reviewers, bloggers and others. All of that can be targeted for those who actively use the internet or are often referred to as citizens. Social media is a vital marketing and communication channel for businesses, organizations and institutions that are included in the political sphere. In addition, social media in terms of culture is very important because it has become one of the most dominated parts of people where they can receive large amounts of information, share content and also all aspects of their lives with others, and receive information about the world around them ( although that information might have questionable accuracy).Keyword: Social media in marketing